2021
DOI: 10.3390/nano11051276
|View full text |Cite
|
Sign up to set email alerts
|

The Efficient Photocatalytic Degradation of Organic Pollutants on the MnFe2O4/BGA Composite under Visible Light

Abstract: The MnFe2O4/BGA (boron-doped graphene aerogel) composite was prepared by hydrothermal treatment of MnFe2O4 particles, boric acid, and graphene oxide. When applied as a photo-Fenton catalyst for the degradation of rhodamine B, the MnFe2O4/BGA composite yielded a degradation efficiency much higher than the sum of those of individual MnFe2O4 and BGA under identical experimental conditions, indicating a strong synergetic effect established between MnFe2O4 and BGA. The catalytic degradation of rhodamine B was prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Moreover, the electronic structure of GA could be easily adjusted by the covalent modification of some other non-metal elements, and a synergistic effect between the doped GA and the semiconducting photocatalyst often appears in the process of photocatalysis. For example, Chanez et al [28] reported the enhancement of visible-light photocatalytic pollutant degradation and hydrogen evolution with a 3D nitrogen-doped GA (N-GA), and Ren et al [29] evidenced the rapid degradation of tetracycline on the spinel CoFe 2 O 4 nanoparticles anchored on N-GA. On the other hand, the BGA displayed a superior efficiency to GA towards the degradation of acridine orange under visible light irradiation [30], and we reported previously that a strong synergetic effect established between MnFe 2 O 4 and BGA during the degradation of rhodamine B on the MnFe 2 O 4 /BGA [31].…”
Section: Introductionsupporting
confidence: 57%
“…Moreover, the electronic structure of GA could be easily adjusted by the covalent modification of some other non-metal elements, and a synergistic effect between the doped GA and the semiconducting photocatalyst often appears in the process of photocatalysis. For example, Chanez et al [28] reported the enhancement of visible-light photocatalytic pollutant degradation and hydrogen evolution with a 3D nitrogen-doped GA (N-GA), and Ren et al [29] evidenced the rapid degradation of tetracycline on the spinel CoFe 2 O 4 nanoparticles anchored on N-GA. On the other hand, the BGA displayed a superior efficiency to GA towards the degradation of acridine orange under visible light irradiation [30], and we reported previously that a strong synergetic effect established between MnFe 2 O 4 and BGA during the degradation of rhodamine B on the MnFe 2 O 4 /BGA [31].…”
Section: Introductionsupporting
confidence: 57%
“…Nevertheless, bulk MnFe 2 O 4 could not efficiently eradicate heavy metal ions and dyes. In this regard, nano-sized magnetic particles overcome these glitches and can yield bigger specific surface areas, which produce superior adsorption or photocatalytic capacities for the elimination of contamination [ 19 , 20 ]. Nanotextured ferrite is a type of composite oxide with the key constituents of trivalent iron oxides [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…0.4NiO-CeO 2 displayed a type-II isotherm and an H2-type hysteresis loop in the high P/P 0 range of 0.7-1.0. This suggests that it was composed of fractured pore materials with crack-or wedge-shaped porous structures [35]. For FS and 0.4(0.4NiO-CeO 2 )-FS, two similar isotherms in the P/P 0 range of 0-1.0 exhibit a type-II isotherm and inconspicuous H4-type hysteresis loops, evidencing the coexistence of micropores and wedge-shaped meso-/micropores [21].…”
Section: Materials Characterizationmentioning
confidence: 95%